2007
DOI: 10.1080/02667360701660951
|View full text |Cite
|
Sign up to set email alerts
|

Is Victor Better than Victoria at Maths?

Abstract: The aim of this study was to examine whether there are gender differences in actual maths achievement, in attitudes towards maths, and in relevant achievement attributions among early adolescents. The participants were 255 eighth grade students (mean age 14.2) from 10 randomly selected public junior high schools in Cyprus. They completed a questionnaire that measured their attributions of their own maths achievement and their attitudes towards the subject (how attractive and useful it is). Then they took a mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…[38] in a study with secondary school students showed that those with better academic performance have more positive attitudes than those with poorer academic performance. Contrary to this a study conducted by [23] showed that high achievement can serve to predict a positive attitude towards mathematics, but such an attitude cannot predict higher achievement. This phenomenon is revealed in students at secondary and preparatory level, there are students who have positive attitude towards mathematics but their performance is poor [39].…”
Section: Attitude Towards Mathematics and Achievementmentioning
confidence: 66%
“…[38] in a study with secondary school students showed that those with better academic performance have more positive attitudes than those with poorer academic performance. Contrary to this a study conducted by [23] showed that high achievement can serve to predict a positive attitude towards mathematics, but such an attitude cannot predict higher achievement. This phenomenon is revealed in students at secondary and preparatory level, there are students who have positive attitude towards mathematics but their performance is poor [39].…”
Section: Attitude Towards Mathematics and Achievementmentioning
confidence: 66%
“…Nonetheless there is research which concludes that gender does not affect attitudes towards mathematics [3,5,6,15,16]. The meta-analysis conducted by Ma and Kishor [15] which looks at 113 studies (n = 55265), when studying the effects of gender, concludes that this variable did not have a significant effect on the relationships between attitudes and performance in mathematics because separate analysis by gender demonstrated similar significant effect sizes.…”
Section: Gender and Attitudes Towardsmentioning
confidence: 99%
“…Results concerning gender differences in attitudes are less consistent than those in self-concept. Some studies have reported significant differences when we compare girls and boys attitudes towards mathematics [7,[13][14][15], nevertheless there are a number of studies where these differences are not identified [3,5,6,16,17]. A meta-analysis conducted by Etsey and Snetzler [17] taking into consideration 96 studies (n = 30490) concluded that gender differences in student attitudes toward mathematics do exist but are small.…”
Section: Gender and Attitudes Towardsmentioning
confidence: 99%
“…By its findings, this research has joined the school of thought that relates student attitude significantly to student performance. Nevertheless, Georgiou et al (2007) demonstrated that high accomplishment could serve to anticipate an inspirational frame of mind towards Math. However, such a demeanor could not foresee more grounded accomplishment.…”
Section: Neutralmentioning
confidence: 99%